2018
DOI: 10.1590/1678-4324-2017160264
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Ellagic Acid on Nucleus Tractus Solitarius Electrical Activity and Oxidative Stress Altered by Cerebral Global Ischemia/Reperfusion in Rat

Abstract: Cerebral ischemia commonly occurs when the blood flow to the entire brain or some part of the brain is disrupted. Global cerebral ischemia attenuates the nucleus tractus solitaries (NTS) EEG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…16,17 Antosianin dan tannin dapat mengurangi kerusakan biomolekul tubuh akibat proses oksidatif sehingga mampu memperbaiki tekanan darah pada sampel tikus hipertensi. 18 Berdasarkan hasil temuan diatas, peneliti berasumsi bahwa jus buah memiliki potensi yang cukup besar untuk digunakan sebagai terapi komplementer dengan sampel penelitian pasien hipertensi. Terapi yang mungkin aman dalam penggunaan jangka panjang dan dapat membantu menurunkan tekanan darah.…”
Section: Pendahuluanunclassified
“…16,17 Antosianin dan tannin dapat mengurangi kerusakan biomolekul tubuh akibat proses oksidatif sehingga mampu memperbaiki tekanan darah pada sampel tikus hipertensi. 18 Berdasarkan hasil temuan diatas, peneliti berasumsi bahwa jus buah memiliki potensi yang cukup besar untuk digunakan sebagai terapi komplementer dengan sampel penelitian pasien hipertensi. Terapi yang mungkin aman dalam penggunaan jangka panjang dan dapat membantu menurunkan tekanan darah.…”
Section: Pendahuluanunclassified
“…Ellagic acid is a form of tannic acid group and it is a polyphenol compound that is naturallyfound in some fruit and medicinal plants; and it has antioxidant and anti-inflammatory properties; moreover, researchers proved that the EA protect the liver against valproic acid and carbon tetrachloride (CCl4) (5) . Furthermore, EA have the ability to act on electrophysiological activity against traumatic brain damage, and it has a role in neurodegenerative disease like Parkinson's disease (PD) (6) . Additionally, researchers reported that the EA can prevent several types of cancers/breast, skin, and other types; furthermore, it canincrease the antioxidant enzymes and -reduce the pro-inflammatory cytokines through different pathway such its effect on decreasing nuclear factor-kappa B (NF-κB) activity, effect on release the cytochrome c through the potentiate the mitochondrial membrane; and through these methods, which are followed by ellagic acid lead to increase the Caspase-3 and increases expression in the tumor suppressor protein (p21) and then activation of apoptosis and cell cycle regulation (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Although some scientific studies have previously reported on EA-inhibiting lipid peroxidation, and EA's anti-inflammatory, antiproliferative, antiangiogenic, hyperglycemia inhibiting, and anticarcinogenic effects [25][26][27], little information is available on the use of brain metabolomics as a tool for analyzing the integral metabolites of fever with EA. Research is necessary to enable a rat brain metabolomics investigation of the pyrexia and the antipyretic anti-inflammatory effect of EA performed using Ultra-High-Performance Liquid Chromatography-Mass spectrometry (UPLC-MS).…”
Section: Introductionmentioning
confidence: 99%